2017
DOI: 10.1371/journal.pone.0182924
|View full text |Cite
|
Sign up to set email alerts
|

Bile microbiota in primary sclerosing cholangitis: Impact on disease progression and development of biliary dysplasia

Abstract: ObjectiveThe etiopathogenesis and risk for development of biliary neoplasia in primary sclerosing cholangitis (PSC) are largely unknown. Microbes or their metabolites have been suggested to play a role. To explore this potential microbial involvement, we evaluated the differences in biliary microbiota in PSC patients at an early disease stage without previous endoscopic retrograde cholangiography (ERC) examinations, advanced disease stage, and with biliary dysplasia or cholangiocarcinoma.DesignBile samples fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 32 publications
4
74
2
Order By: Relevance
“…In contrast, patients with PSC have marked reductions in Clostridiales II , Prevotella and Roseburia , and Bacteroides , compared to patients with IBD alone and healthy controls . Actinobacteria, Proteobacteria, Streptococcus and Rothia have been reported to be overrepresented in patients with PSC compared with healthy controls and patients with inflammatory bowel disease . Mucosa‐associated bacteria as opposed to stool was also found with a lower bacterial diversity in patients with PSC, with an underrepresentation of an uncultured Clostriadiales II .…”
Section: Interplay Between the Gut Microbiota And Primary Sclerosingmentioning
confidence: 95%
“…In contrast, patients with PSC have marked reductions in Clostridiales II , Prevotella and Roseburia , and Bacteroides , compared to patients with IBD alone and healthy controls . Actinobacteria, Proteobacteria, Streptococcus and Rothia have been reported to be overrepresented in patients with PSC compared with healthy controls and patients with inflammatory bowel disease . Mucosa‐associated bacteria as opposed to stool was also found with a lower bacterial diversity in patients with PSC, with an underrepresentation of an uncultured Clostriadiales II .…”
Section: Interplay Between the Gut Microbiota And Primary Sclerosingmentioning
confidence: 95%
“…27,29 Changes have also been shown in biliary microbiota in this condition. 30 Viral hepatitis: Hepatitis B and hepatitis C have variable impact on gut microbial composition. Studies of HCV-associated liver disease on the microbiota are not very clear with results suggesting that the microbiota changes before cirrhosis and after cirrhosis.…”
Section: Composition and Functional Changes In Microbiota In Patientsmentioning
confidence: 99%
“…Taken together, this hypothetical vicious cycle suggests a new pathogenic mechanism for antibodies encompassing features of types 2 and 3 of hypersensitive immune reactions in accordance with the classification of Coombs and Gell by involving microbiota (coloured oval area). (Adapted according to [62]) [136,137]. A possible involvement of the microbiota in PSC could also be supported by the identification of a genetic polymorphism linked with PSC as well as CD that generated a dysfunctional fucusyltransferase-2 (FUT2) [138,139].…”
Section: Putative Role Of Gp2 Iga In the Pathophysiology Of Pscmentioning
confidence: 99%
“…In PSC, clinical trials demonstrated a beneficial effect of antibiosis on liver enzyme levels [146]. The aetiology of PSC does not appear to be associated with specific changes in biliary microbial communities [136]. However, the genus Streptococcus is considered to play a putative role in the progression of PSC.…”
Section: Putative Role Of Gp2 Iga In the Pathophysiology Of Pscmentioning
confidence: 99%